Can conditional cash transfers boost trust within communities? In Tanzania, they did - Evans, David; Kosec, Katrina (Center for Global Development, 2022)
When we began working with the government of Tanzania to evaluate a pilot conditional cash transfer program, we heard similar concerns from policymakers: would cash transfers provided by the state erode informal safety nets? After several years of evaluation, the answer appears to be no.